Cardiac Shockwave Therapy – A Novel Therapy for Ischemic Cardiomyopathy? - Graber, Michael; Nägele, Felix; Hirsch, Jakob; Pölzl, Leo; Schweiger, Victor; Lechner, Sophia; Grimm, Michael; Cooke, John P.; Gollmann-Tepeköylü, Can; Holfeld, Johannes (Frontiers in Cardiovascular Medicine, 2022)
Over the past decades, shockwave therapy (SWT) has gained increasing interest as a therapeutic approach for regenerative medicine applications, such as healing of bone fractures and wounds. More recently, pre-clinical studies have elucidated potential mechanisms for the regenerative effects of SWT in myocardial ischemia. The mechanical stimulus of SWT may induce regenerative effects in ischemic tissue via growth factor release, modulation of inflammatory response, and angiogenesis. Activation of the innate immune system and stimulation of purinergic receptors by SWT appears to enhance vascularization and regeneration of injured tissue with functional improvement. Intriguingly, small single center studies suggest that SWT may improve angina, exercise tolerance, and hemodynamics in patients with ischemic heart disease. Thus, SWT may represent a promising technology to induce cardiac protection or repair in patients with ischemic heart disease.